Developing a regional cooperation strategy for scaling up climate-smart agriculture in South Asia - Sawhney, Aparna; Sma, Abdelkarim; Pradhan, Mamata; Kamar, Abul; Roy, Devesh (International Food Policy Research Institute, 2025)
Climate change being a global environmental problem, a cooperative approach involving all the sovereign countries is required to achieve an optimal solution. Caused by the accumulation of greenhouse gases (GHG) in the atmosphere, including carbon dioxide, methane, nitrous oxide, and hydrofluorocarbons, climate change has global effects that are independent of the geographical sources of these emissions. However, the adverse impacts of global warming and extreme weather events associated with climate change are not uniformly distributed, as vulnerable populations in less-developed countries bear the brunt of the damage. Some of these climate-vulnerable nations contribute less than 1 per cent of global GHG emissions, including Bhutan (0.0057%), Sri Lanka (0.072%), Nepal (0.105%), and Bangladesh (0.522%) in South Asia.